Use impregnation and densification to improve mechanical properties and combustion performance of Chinese fir. (30th April 2020) - Yue, Kong; Wu, Jinhao; Xu, Liqin; Tang, Zhongqiu; Chen, Zhangjing; Liu, Weiqing; Wang, Lu
Highlights: The plantation wood was modified by combined of resin and densification. The strength class of treated wood by compound modification was increased greatly. The fire resistance by compound modification was improved significantly. The relationship between selected properties and microscopic images was built. Abstract: The abundant fast-growing Chinese fir is a low-grade building material due to its low mechanical strength and poor combustion performance. The impregnation with boric phenol formaldehyde resin ( BPF ) improve the mechanical properties and combustion performance in laboratory. Chinese fir wood was thermos-mechanically densified in laboratory scale with varying compression ratios after wood was impregnated with BPF resin with a concentration of 30%. The effects of the combination of BPF resin impregnation and compression ratio on mechanical properties and combustion performance were discussed. The test results have showed that the mechanical properties at high temperature and combustion performance were improved significantly. The higher the compression ratio, the better the mechanical properties and combustion performance of the BPF -densified-specimen.